Possessors and Possessed : Museums, Archaeology, and the Visualization of History in the Late Ottoman Empire - Shaw, Wendy M. K., 1970- (Book collections on Project MUSE., 2003)
This work analyses how and why museums emerged in the late 19th century Ottoman Empire. It argues that Ottoman elites produced categories of collection and modes of display appropriate to framing a new identity for the empire in the modern era rather than emulating museums in Western Europe.